Features of formation and development of student sports in China - Kuang Yixin (Theory and Practice of Physical Culture, 2025)
On the large scale of China (PRC) establishment, physical education in the country has a nearly 70-years history, evolving from simple to complex, adjusting and giving a rise to various sub-disciplines. This research reveals chronology of school physical education in New China through different periods, analyzes prominent impact of policy amendment, and reflects on its epoch-making course of development. By exploring the history of school sports, we gain insights into China’s education system, the role of sports in nation-building, and their great influence on youth health and spirits, as well as high educational standards. Taking into consideration a thorough study of Chinese and foreign literature, we define three stages of growth: the initial phase (1949-1976), the period of reform and recovery (1977-2008), and the era of discipline development (2009-present).